Opening the black box of the relationship between neighborhood socioeconomic status and mental health: Neighborhood social-interactive characteristics as contextual mechanisms. (September 2022) - Jakobsen, Andreas Lindegaard; Jørgensen, Anja; Tølbøll, Lene; Johnsen, Sisse Buch
Abstract: Previous studies have linked low neighborhood socioeconomic status (NSES) to mental health problems. However, few studies have investigated the mechanisms underlying this association and most focused on the association with negative indicators of mental health, such as symptoms of depression or anxiety. This paper investigated whether neighborhood social characteristics (social interaction, trust, safety, organization participation, and attachment) mediate the association between NSES and mental health. We combined Danish register data with survey data from the North Denmark Region Health Survey 2017. Mental health was assessed with the Rand 12-item Short-form Survey (SF-12). The sample consisted of 14, 969 individuals nested in 1047 neighborhoods created with an automated redistricting algorithm. We fitted multilevel structural equation mediation models and used a Monte Carlo simulation method to estimate confidence intervals for the indirect effects. NSES was positively associated with mental health. Neighborhood trust significantly mediated this relationship, accounting for 34% of the association after controlling for other mediators. These results indicate that higher levels of mental health in more affluent neighborhoods are partially explained by higher levels of trust. Improving neighborhood trust could mitigate sociogeographic inequalities in mental health. Highlights: Neighborhood socioeconomic status was positively associated with mental health. Multiple mediators were tested using a multilevel structural equation framework. Trust mediated the neighborhood socioeconomic status and mental health relationship.